Total arterial myocardial revascularization (one center experience) - O. I. Pukas; S. V. Varbanec; O. M. Dovgan (Ukrainian Journal of Cardiovascular Surgery, 2018)
Today gold standard of surgical treatment of ischemic heart disease is coronary artery bypass surgery (or graft, CABG) with the use of left internal thoracic artery (LITA) and great saphenous vein (GSV) of the lower limb.Objective of the work is to show own experience of performing total arterial myocardial revascularization of patients with isolated multi vascular defeat of coronary artery, in combination with concomitant pathology of the heart valves.Materials and methods From January 2001 to December 2017 in State Institution «Scientific-Practical Medical Center of Pediatric Cardiology and Cardiac Surgery» Ministry of Health of Ukraine 91 patients were operated, as treatment of ischemic heart disease was performed full arterial vascularization of coronary arteries. All examined patients have two- and more vascular defeat of coronary artery.Results and discussions. So due to our experience it should be mentioned that two and more arterial conduits CABG is safety, and doesn’t take too much time and could be performed in most patients with ischemic heart disease. According to our data there is no strict contraindications of total arterial myocardial revascularization perfoming. But in five, in ten years should graft potency be tested.Conclusions. Some patients with traditional contraindications to total arterial myocardial revascularization as: overweight (BMI>35), chronic obstructive pulmonary disease, insulin-dependent diabetes mellitus could have (be performed) optimal type of bypass after additional examination.